2016
DOI: 10.15640/ijlc.v4n1a7
|View full text |Cite
|
Sign up to set email alerts
|

Mind Mapping Techniques to Enhance EFL Writing Skill

Abstract: The study identifies appropriate Mind mapping techniques to enhance the EFL learners' writing ability. It reviews and examines the traditional techniques used in teaching writing to the Saudi intermediate learners and identifies appropriate Mind mapping techniques along with an application procedure to enhance the writing skill. The sample included 40 intermediate learners and 20 English language teachers at the English Language Institute. The study divided into two phases; a Survey Phase and an Experiment Pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 3 publications
5
40
0
2
Order By: Relevance
“…Mind mapping was used as the note, graphic organizer, and controller of the students' ideas for writing. As concluded by Bukhari (2016) that the learners who were taught through Mind maps, improved cohesion and coherence; content paragraph structure and length in writing. However, when it is implemented individually, it is assumed less effective because the students only organize their own limited ideas.…”
Section: Discussionmentioning
confidence: 99%
“…Mind mapping was used as the note, graphic organizer, and controller of the students' ideas for writing. As concluded by Bukhari (2016) that the learners who were taught through Mind maps, improved cohesion and coherence; content paragraph structure and length in writing. However, when it is implemented individually, it is assumed less effective because the students only organize their own limited ideas.…”
Section: Discussionmentioning
confidence: 99%
“…Learners' learning capacities, differences, and individual Zone of Proximal Development (Vygotsky, 1978, p. 86) are the most important grounds to know and to reach an individual successfully. According to Bukhari (2016;2019), the hidden talent can be ignited, and untapped learning potentials can be explored provided that the productive interaction and constructive environment are available for all. By using an experimental design, Yurdal and Ülkü Eser (2013) investigate the effect of the use of virtual classroom and blended learning on students' achievement and their attitudes compared to the face-to-face method.…”
Section: Explainsmentioning
confidence: 99%
“…She maintained that numerous studies support the fact that those learners suffer from problems in composing a well-organized piece of text. Alghizzi (2017) emphasized that, though EFL instructors are constantly trying to develop EFL writers, their efforts are limited to examining, for example, the impact of applying various types of tools (e.g., blogs, mind-mapping software, websites), contexts (e.g., traditional, blended, and virtual classrooms), and supplementary materials (e.g., Alnufaie & Grenfell, 2012;Bukhari, 2016;Fageeh, 2011;Grami, 2012;McMullen, 2009;Sayed, 2010). Additionally, in another study, Alghizzi (2012) confirmed that Saudi EFL instructors do not employ a specific writing approach to teach writing.…”
Section: The Importance Of the Process Genre Approach And Caf Measuresmentioning
confidence: 99%